#### Answer

-7$x^{2}$-2x-5.6

#### Work Step by Step

($x^{2}$-x+1.1)+(-8$x^{2}$-x-6.7)
=$x^{2}$-x+1.1-8$x^{2}$-x-6.7
=-7$x^{2}$-2x-5.6

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

-7$x^{2}$-2x-5.6

($x^{2}$-x+1.1)+(-8$x^{2}$-x-6.7)
=$x^{2}$-x+1.1-8$x^{2}$-x-6.7
=-7$x^{2}$-2x-5.6

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.